The body of interactive architecture. Scenario-based and generative approaches - Bianca Andaloro (Agathón)
The complexity of reality, both physical and virtual, in which we are immersed requires a reflection on how to achieve integration between the digital world and contemporary architecture. In particular, the article intends to explore the way in which virtual information can become design material, also intervening on the spatial and formal characteristics of the built environment. Therefore, two different approaches in interactive architectures will be discussed, one scenario-based and the other generative, capable of establishing the physical boundaries of the relationship between architecture and information. Jade Eco Park, Translated Geometries and One Ocean Pavilion offer a different key to interpreting the relationship between man, building and surrounding environment, in a meta-textual relationship between the physical and the virtual that calls contemporary architecture to reflect on the potential of this phenomenon.